Geothermal investigation uses a dipoledipole configuration geoelectric methods with delphi programming - Ariyanto, Sandy Vikki; Joni, Idon; Prasetyowati, Erwin; Susilo, Adi; Yunanto, Fredy (Eastern-European Journal of Enterprise Technologies, 2019)
The position of Indonesia which is located at the confluence of three plates (Eurasia, Indies Australia, and the Pacific) causes the formation of a series of volcanoes in some parts of the country and causes the formation of geothermal energy sources around the volcano. Geothermal energy is the energy of natural resources in the form of hot water or steam formed in a reservoir inside the earth through heating of subsurface water by igneous rocks (Team Pertamina, 2010). This geothermal energy can be used directly for drying agricultural production, tourism, and household needs or indirectly as a driver of electricity-generating turbines. In this study focused in East Java, the author discusses geothermal potential by using geoelectric methods in the never-ending area of fire to contribute manifestation information as one of the answers to the community and government which is expected to provide an idea of how large geothermal potential is using the geoelectric method in the fire area has never been extinguished by Pamekasan Madura. the distance between the 5-meter electrode. The long-term goal of this research is to obtain petroleum fuel energy in the pamekasan area. Geothermal research has been carried out on fire tours. This research uses the dipole-dipole configuration geoelectric method with the help of Delphi program. The results of this program are suitable for time-efficient calculations for geoelectric data processing. This program is equipped with Wenner, Schlumberger, dipole-dipole and pole-pole configuration options so that we can choose the configuration we need. the results of this study are Line 1 stretching from North to South. The subsurface line 1 has a low resistivity of 72.3 Ωm–98 Ωm. the resistivity value of this layer is a reservoir carrier with a depth of 12.8–78.8 meters below the soil surface. Line 2 stretches from east to west. The subsurface layer 2 has a low resistivity of 75.5 Ωm–112 Ωm. the resistivity value of this layer is a reservoir carrier with a depth of 2.5–67.5 meters below the soil surface. Line 3 is a line that runs from east to west. The subsurface layer 3 has a low resistivity of 94.2 Ωm–110 Ωm. the resistivity value of this layer is a reservoir carrier with a depth of 10.5–24.9 meters below ground level